Festucalex bifasciatus, a new pipefish (Teleostei: Syngnathidae) from northern Australia - Yuki, Daijiro; Motomura, Hiroyuki (Zootaxa, 2026)
The new pipefish Festucalex bifasciatus sp. nov., described from eight specimens [89.8–152.8 mm standard length (SL)] collected from Western Australia and Queensland, Australia, and most closely resembling F. cinctus (Ramsay 1882) (11 specimens, 48.8–126.8 mm SL) and F. scalaris (Günther 1870) (10 specimens, 45.4–162.7 mm SL), differs from all members of Festucalex in having 19 or 20 trunk rings; 34–38 tail rings; 24–28 dorsal-fin rays; 12–15 pectoral-fin rays; snout length (SnL) 46.4–52.6% of head length (HL); snout depth 17.8–22.7% of SnL; postorbital length 60.0–74.6% of SnL; lateral trunk ridge ending at second or third tail ring; subadults and adults with or without indistinct ridges on pectoral-fin base; principal ridges of last 1 or 2 tail rings with 1–7 knobs or projections; and opercle with 2 white bars (2 pale bars in preserved specimens). The new species was mostly collected by dredge at depths of 9–81 m. Among all congeners, only F. cinctus shares with the new species the presence of knobbed principal tail ridges, and the two taxa have a broadly overlapping distribution in Australian waters, suggesting a close phylogenetic relationship.